Perancangan Ulang Gedung Kesenian Kota Tasikmalaya Dengan Pendekatan Arsitektur Fleksibel - Dwi Maharani, Gina; Aulia Widyaevan, Dea; Puspa Nabila, Ganesha (Telkom University, 2024)
The redesign of the Tasikmalaya City Arts Building aims to create a multifunctional space that provides optimal facilities to support various arts performances as well as adding complementary commercial facilities for the community with the aim of ensuring the building remains active and functional even when there are no performances taking place. To overcome these challenges, it is necessary to redesign the Arts Building in Tasikmalaya City with an approach of applying flexible architectural technology to create spaces that can accommodate various activities effectively and eficiently, including the application of adaptive and appropriate technology such as sound, lighting and space flexibility. Sound technology includes acoustic ceilings, materials, variable acoustics, audio settings and controls. Lighting technology includes various types of lamps, lighting controls and scenario-based lighting tailored to specific activities, as each activity directly influences space requirements and conditioning, thereby impacting the redesign of the Arts Building in Tasikmalaya City. Keywords : performance hall, arts hall, multi activity, technology, flexible